Implementation stages in practice: A review of behavioral health innovation within hospitals - Domlyn, Ariel M (Health services management research, 2022)
Behavioral health influences patient health outcomes and healthcare utilization rates. Hospitals are promising settings for appropriate identification, treatment, and referral of behavioral health issues and may affect hospital admission rates and healthcare costs. Implementation frameworks are designed to aid successful adoption and scaling of health innovations. One type - process models - present staged frameworks for rolling out an innovation into routine practice. Process models are appealing for their pragmatism but are criticized for oversimplifying the complexity of implementation. This review investigates the empirical evidence for process models' utility in hospitals, chosen for their uniquely complex structures, by determining whether their use impacts implementation outcomes. Using systematic search and selection criteria across six databases, ten peer-reviewed studies were identified. Each applied a process model for implementing behavioral health innovations within hospital systems. Studies were coded by type of stage framework and reported implementation outcomes. Studies reported mostly favorable or mixed outcomes. No one framework prevailed in use nor evidence. Due to the paucity of published literature and reported data, there is limited evidence that process model application propels implementation outcomes in hospital settings. Furthering the science requires creating and utilizing systematic guidelines to employ process models, measure and report implementation stage transition, and measure and report implementation outcomes. Management and practitioners can include such data collection in standard process evaluations of hospital implementation and scale-up activities, or adopt complexity-informed approaches that lack the simplicity of process models but may be more realistic for complex settings.